1, 1-Difluoroethyl chloride (CH3CF2Cl), a novel difluoroalkylating reagent for 1, 1-difluoroethylation of arylboronic acids. Issue 49 (9th September 2019) - Liu, Jianchang; Zhang, Jida; Wu, Chaolin; Liu, Hefu; Liu, Hui; Sun, Fenggang; Li, Yueyun; Liu, Yuying; Dong, Yunhui; Li, Xinjin
Abstract : 1, 1-Difluoroethylated aromatics are of great importance in medicinal chemistry and related fields. Abstract : 1, 1-Difluoroethylated aromatics are of great importance in medicinal chemistry and related fields. 1, 1-Difluoroethyl chloride (CH3 CF2 Cl), a cheap and abundant industrial raw material, is viewed as an ideal 1, 1-difluoroethylating reagent, but the direct introduction of the difluoroethyl (CF2 CH3 ) group onto aromatic rings using CH3 CF2 Cl has not been successfully accomplished. Herein, we disclose a nickel-catalyzed 1, 1-difluoroethylation of arylboronic acids with CH3 CF2 Cl for the synthesis of (1, 1-difluoroethyl)arenes.